EP1118 Patient-derived ovarian cancer organoids resemble clinical response to chemotherapeutics and provide insights into response mechanisms. (1st November 2019) - de Witte, CJ; Stelloo, E; Hami, N; Espejo Valle-Inclan, J; Lõhmussaar, K; Kopper, O; Vreuls, C; Jonges, T; van Diest, PJ; Clevers, H; Snippert, HJG; Kloosterman, WP; et al.
Abstract : Introduction/Background: Epithelial ovarian cancer is characterized by intratumour genetic heterogeneity, chemotherapy resistance and poor survival. The advent of ovarian cancer organoids, that recapitulate histological and genetic features of the original lesions, has providedopportunities for personalized assessment of drug response. Here, we assessed if the ovarian cancer organoid system can predict patients' clinical response to chemotherapeutics. In addition, we evaluated the link between intratumour genetic heterogeneity and drug response using multiple organoids derived from individual patients. Methodology: In total, we included 34 organoid lines derived from 22 patients with ovarian cancer at primary surgery or interval debulking. Organoid drug responses to chemotherapeutics as well as targeted drugs were determined. The IC50 and area under the curve values were computed from the drug response curves. Patients' recurrence-free and overall survival were compared to the organoid drug response. For patients who received carboplatin and paclitaxel chemotherapy prior to interval debulking (N=7), we additionally compared organoid drug response to biochemical (CA125), pathological, radiological outcomes. The organoids and corresponding tumour tissues were subjected to whole genome sequencing for genomic analysis. Results: Organoid drug response correlated to clinical response as defined by histopathological tumour assessment (chemotherapy response score (CRS)). Organoids of patients with no or minimal pathological response (CRS=1) were less sensitive to carboplatin and paclitaxelcompared to organoids of the patients with appreciable pathological response (CRS=2). The presumed additive effect of paclitaxel on carboplatin was only observed in a subset of organoids. Organoid exposure to eight additional drugs revealed that multiple tumour locations of the same patients exhibited varying responses to specific drugs. Genomic analyses are being performed to identify underlying mechanisms of differential drug responses. Conclusion: Ovarian cancer organoids provide a valuable preclinical system with the potential to guide treatment choice through prediction of drug response, avoid unnecessary overtreatment and provide insights in response mechanisms. Disclosure: No competing interests. Applicable funding sources: EIF | Stand Up To Cancer (SU2C) [Clevers, Kopper] KWF Kankerbestrijding (Dutch Cancer Society) - UU2015-7743 [de Witte, Witteveen, Zweemer, Kloosterman] Gieskes Strijbis Foundation (1816199) [Clevers, Witteveen, Kloosterman, Zweemer, Lõhmussaar, Espejo Valle-Inclan, Hami, Snippert]